DIGITAL TOOLS TO PROMOTE BANTENGAN ART: KEBO PUTRO JOYO ANOM CASE STUDY - Kusumawati, Yudhistya Ayu; Yongkie Angkawijaya; Bhekti Setyo Wibowo (Bina Nusantara University, 2025)
There are various kinds of culture in Indonesia, especially the local culture. It's not surprising that many young and old people take part in maintaining local culture, one of which is Bantengan art. Bantengan art is widely known by people who love traditional culture. The traditional art of Bantengan comes from East Java, combining elements of ballet, kanuragan, music, and thick poetry or mantras with a magical feel. The game will be interesting if it enters the trance stage, namely the stage where the player holding the Bull's head becomes possessed by the spirit of the Bull's ancestors. The Kebo Putro Joyo Anom Bantengan Art Group is one of the many Bantengan art groups in Malang Regency. The preservation of traditional arts, such as Bantengan, is crucial for cultural heritage and community identity. However, the challenges of modern times, including rapid urbanization and globalization, threaten the continuity of these art forms. To address this issue, this research explores the potential of digital tools to promote and preserve Bantengan art within the Kebo Putro Joyo Anom art group in Malang District, East Java. By leveraging digital platforms and technologies, the study aims to create a more accessible and engaging experience for both artists and audiences, fostering a deeper appreciation for Bantengan art and ensuring its legacy for future generations.